2018
DOI: 10.1186/s40634-018-0122-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of meniscal repair for prevention of early onset of osteoarthritis

Abstract: BackgroundThe meniscus plays an important role in the integrity of the knee joint. Therefore, meniscus tissue preserving techniques for the therapy of meniscus injuries seem to be reasonable. One of the important questions is whether meniscal repair can prevent the knee joint from early onset of osteoarthritis.MethodsAccording to the review of the current literature, the principles of a successful meniscal repair are explained and the functional outcome and its impact on the prevention of osteoarthritis are an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 43 publications
2
40
0
2
Order By: Relevance
“…The menisci always bear an extremely high stress in every posture of the gait cycle. The meniscus tear in a healthy knee may eventually result in the occurrence of knee OA due to the meniscus dysfunction and the consequent overloading in the intraarticular space [39], [40]. According to the results of previous case–control studies, OA is more likely to occur in a knee with meniscal tears but without cartilage lesions than in a knee with an intact meniscus, indicating that the meniscal tear comes before any visible cartilage changes can be noted [33], [41].…”
Section: Discussionmentioning
confidence: 99%
“…The menisci always bear an extremely high stress in every posture of the gait cycle. The meniscus tear in a healthy knee may eventually result in the occurrence of knee OA due to the meniscus dysfunction and the consequent overloading in the intraarticular space [39], [40]. According to the results of previous case–control studies, OA is more likely to occur in a knee with meniscal tears but without cartilage lesions than in a knee with an intact meniscus, indicating that the meniscal tear comes before any visible cartilage changes can be noted [33], [41].…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 The importance of meniscus repair is in keeping with past literature. 8 , 9 Johnson et al found that at almost 11 years after isolated meniscus repair, minimal joint changes were seen in only 8% of his patients on the surgical knee with 3% of patients having changes also on the contralateral side. He evaluated radiographs and found joint changes in 69% of his patients after a meniscectomy was done.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring or preserving the normal anatomy of the knee leads to restoration of function but can also return knee biomechanics to the intact state. 5 6 7 8 9 This in turn can reduce loading and sheer forces on the hyaline cartilage. 10 , 11 Many surgeries were done that seek to restore the normal structure and function of the knee.…”
mentioning
confidence: 99%
“…Таким чином, є прямий взаємозв'язок між відновленням цілісності меніска та профілактикою раннього прогресування деформуючого артрозу колінних суглобів. Однак невірне передопераційне планування та вибір тактики лікування пошкоджень меніска підвищують ризик повторного оперативного лікування [10].…”
Section: вступunclassified